2021
DOI: 10.1111/bph.15536
|View full text |Cite
|
Sign up to set email alerts
|

cGMP and mitochondrial K+ channels—Compartmentalized but closely connected in cardioprotection

Abstract: Abbreviationscoronary artery disease (CAD), cardiomyocyte (CM); electron transport chain (ETC); fluorescence resonance energy transfer (FRET); heart failure (HF); hypoxia and reoxygenation (H/R); inner mitochondrial membrane (IMM); ischemia and reperfusion (I/R); ischemic post-conditioning (iPost); ischemic pre-conditioning (iPre); mitochondrial membrane potential (ΔΨm); mitochondrial permeability transition pore (mPTP); myocardial infarction (MI); percutaneous coronary intervention (PCI); reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 153 publications
(295 reference statements)
0
6
0
1
Order By: Relevance
“…Следует подчеркнуть, что на протяжении годичного цикла тип регуляции сердечной деятельности у элитных лыжников не меняется. Это позволяет сформулировать представление о том, что специализация вида спорта, которую выбирает начинающий спортсмен, зависит от индивидуальных особенностей регуляции сердечной деятельности, в которой принимают участие не только ПО и СО АНС, но и многие другие медиаторы и БАВ, например, эндогенные антиоксиданты, в том числе ферменты-антиоксиданты типа супероксидисмутазы [45], эндогенные сенсибилизаторы бета-адренорецепторов, или ЭСБАР, в том числе гистидин, триптофан и тирозин [46], а также дофамин [47], серотонин [48], простагландины [49], оксид азота [50], ненейрональный ацетилхолин [4,5,51], и другие гормоны и медиаторы, проявляющие свойства антиоксидантов и антиапоптических факторов, например, мелатонин [52]. Все вместе они, вероятно, образуют антиапоптическую систему, которая препятствует апоптозу кардиомиоцитов в условиях высокой физической нагрузки, т.е.…”
Section: Discussionunclassified
“…Следует подчеркнуть, что на протяжении годичного цикла тип регуляции сердечной деятельности у элитных лыжников не меняется. Это позволяет сформулировать представление о том, что специализация вида спорта, которую выбирает начинающий спортсмен, зависит от индивидуальных особенностей регуляции сердечной деятельности, в которой принимают участие не только ПО и СО АНС, но и многие другие медиаторы и БАВ, например, эндогенные антиоксиданты, в том числе ферменты-антиоксиданты типа супероксидисмутазы [45], эндогенные сенсибилизаторы бета-адренорецепторов, или ЭСБАР, в том числе гистидин, триптофан и тирозин [46], а также дофамин [47], серотонин [48], простагландины [49], оксид азота [50], ненейрональный ацетилхолин [4,5,51], и другие гормоны и медиаторы, проявляющие свойства антиоксидантов и антиапоптических факторов, например, мелатонин [52]. Все вместе они, вероятно, образуют антиапоптическую систему, которая препятствует апоптозу кардиомиоцитов в условиях высокой физической нагрузки, т.е.…”
Section: Discussionunclassified
“…Undoubtedly, this observation served as a pivotal starting point for numerous experiments identifying ATP-regulated mitochondrial potassium (mitoK ATP ) channels across various tissues, notably cardiomyocytes ( Szewczyk et al, 2009 ; Szabo and Szewczyk, 2023 ). Following several years of intensive investigation across multiple laboratories into the functional role of these channels, it was demonstrated that the activation of mitoK ATP channels (by potassium channel openers) induces a cardioprotective phenomenon ( Liu et al, 1999 ; Garlid, 2000 ; Szteyn and Singh, 2020 ; Lukowski et al, 2022 ). Subsequently, similar findings in neural tissue suggested the involvement of these channels in neuroprotection ( Busija et al, 2004 ; Bednarczyk, 2009 ).…”
Section: Mitochondrial Potassium Channel Discoverymentioning
confidence: 99%
“…During MI and I/R, cGMP triggers cytoprotective responses and improves cardiomyocyte survival; cGMP production leads to the activation of cGKI, which in turn phosphorylates many substrates and eventually facilitates the opening of mitochondrial ATP-sensitive K channels and Ca-activated K channels of the BK type [ 131 , 132 ]. PDEs and SERCA2, which were mentioned above as downstream molecules in the CNP/NPR-B signaling cascade in the failing heart, are thought to be effective in MI states because the in vitro experimental model of heart failure included ventricular cardiomyocytes from Wistar rats with heart failure after MI [ 99 , 119 ].…”
Section: Roles Of Cnp On MImentioning
confidence: 99%